Expression and Function of Fibroblast Growth Factor 18 in the Ovarian Follicle in Cattle - Portela, Valerio M.; Machado, Mariana [UNESP]; Buratini, Jose [UNESP]; Zamberlam, Gustavo; Amorim, Renee L. [UNESP]; Goncalves, Paulo; Price, Christopher A. (Soc Study Reproduction, 2010)
Fibroblast growth factors (FGF) are involved in paracrine signaling between cell types in the ovarian follicle. FGF8, for example, is secreted by oocytes and controls cumulus cell metabolism. The closely related FGF18 is also expressed in oocytes in mice. The objective of this study was to assess the potential role of FGF18 in follicle growth in a monovulatory species, the cow. Messenger RNA encoding FGF18 was detected primarily in theca cells, and in contrast to the mouse, FGF18 was not detected in bovine oocytes. Addition of FGF18 protein to granulosa cell cultures inhibited estradiol and progesterone secretion as well as the abundance of mRNA encoding steroidogenic enzymes and the follicle-stimulating hormone receptor. In vivo, onset of atresia of the subordinate follicle was associated with increased theca! FGF18 mRNA levels and FGF18 protein in follicular fluid. In vitro, FGF18 altered cell cycle progression as measured by flow cytometry, resulting in increased numbers of dead cells (sub-G1 peak) and decreased cells in S phase. This was accompanied by decreased levels of mRNA encoding the cell cycle checkpoint regulator GADD45B. Collectively, these data point to a unique role for this FGF in signaling from theca cells to granulosa cells and suggest that FGF18 influences the process of atresia in ovarian follicles.
Keywords: follicle; granulosa cells; growth factors; ovary